Is the orthodontic smile considered as aesthetic in adult patients? - Mello, Gabriela; Evangelista, José Grillo; Alves, Valter Pedroso; Delgado, Ana Sintra; Dias, Maria do Rosário (Corpus Publishers, 2023)
In the last five years, pioneer studies were carried out in the Egas Moniz University Clinic surrounding the mental representation of the smile, centred on adolescent patients wearing orthodontic appliances, emerging with the results obtained as a new form of categorizing the perfect smile: The Orthodontic Smile. The present study is qualitative and exploratory and aims to understand the importance of the self-perception (mental representation) of the smile, now with the help of a new age range - Adult Patients. The sample consists of 100 subjects in the adult phase (25–59 y), namely patients wearing orthodontic appliances who were asked to draw two percepts about the self-perception of their own smile in two distinct moments: the first drawing, corresponding to before the wear of the orthodontic appliance (M1), and the second one, corresponding to drawing their smile after undergoing the orthodontic treatment (M2). The content analysis of the 200 drawings obtained was realized through a grid of content analysis, constituted by categories and subcategories. The patients also filled out a sociodemographic questionnaire, in which they responded to four open-ended questions in relation to the mental representation of the smile. Regarding the content analysis of the narrative, we highlight the fact that a Nice Smile seems to be mostly described as a Natural Smile and Aligned, being a motive for the seeking of dental treatment, primarily aesthetic issues, followed by functional considerations. When comparing the drawings before (M1) and after (M2) the wear of orthodontic appliances, the Category Broad Smile, is set up as the smile chosen as the most aesthetic. It seems that aesthetic motives represent the motivational power for the patient in the adult phase, when they decide to look for Orthodontic treatment.
Distributed under Creative Commons Licence CC-BY 4.0
Keywords: Mental Representation; Orthodontic Smile; Perfect Smile; Orthodontic Appliances; Drawings; Adult Patients